Ocio desviado, juego on line y su víctima: este partido está amañado: ¿y tus apuestas? = Deviant leisure, Online games and its victim: this match is fixed : and your bets? - Ríos Corbacho, José Manuel (Revista de victimología, 2025)
The corruption established in our society is also reflected in sports. We are experiencing tumultuous times in this matter. At the end of each sports season, the ghosts of match-fixing and other types of sports confrontations return through an infinite world, such as that of betting, where enormous economic benefits are obtained, greatly expanded through the internet. This work aims to address the issue of match-fixing and the profile of online gambling victims, as well as how criminal law intervenes to prevent this problem in order to safeguard fair play in the sports field.